2016
DOI: 10.1108/scm-07-2015-0266
|View full text |Cite
|
Sign up to set email alerts
|

The influence of supply chain on the innovation process: a systematic literature review

Abstract: Purpose The importance of innovation as a generator of competitive advantage and the collaborative nature of this process are recurring themes in the literature. This paper aims to contribute to the improvement of knowledge about the relationship between supply chains and the innovation process by means of a systematic literature review. Methodology/approach The method used consists of the identification, selection, analysis and synthesis of existing research on the subject and aims to ensure that the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 64 publications
(124 reference statements)
4
88
0
3
Order By: Relevance
“…Our research revealed the facilitative role of the four dimensions of power (Hardy, 1996) within knowledge integration for innovation projects in supply chains and their inter-dimensional relationships, thereby also addressing a call for empirical studies of innovation facilitators in supply chains (Zimmermann et al, 2016). It confirms Swan and Scarbrough's (2005) suggested applicability of the power of the system to knowledge integration in supply chains.…”
Section: Resultssupporting
confidence: 71%
“…Our research revealed the facilitative role of the four dimensions of power (Hardy, 1996) within knowledge integration for innovation projects in supply chains and their inter-dimensional relationships, thereby also addressing a call for empirical studies of innovation facilitators in supply chains (Zimmermann et al, 2016). It confirms Swan and Scarbrough's (2005) suggested applicability of the power of the system to knowledge integration in supply chains.…”
Section: Resultssupporting
confidence: 71%
“…According to resource-based theory, valuable, rare, and inimitable resources determine the firm's sustainable competitive advantage (Barney, 1991), and the firm needs to explore, utilize, and integrate different special knowledge from external R&D activities and internal resources (Grant, 1996). As suggested by Zimmermann, Ferreira, and Moreira (2016), a firm needs to obtain knowledge resources from external partners to enhance innovation. Ardito, Petruzzelli, Pascucci, and Peruffo (2019) and Liao and Long (2019) also highlighted the importance of cooperation with external partners, which enable firms to acquire external knowledge and develop green innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation is considered the main way to achieve economic growth and competitiveness (Lawson & Samson, 2001;Zimmermann et al, 2016). A distinct concept of innovativeness, "innovation" is the capacity to develop and implement new products (Ettlie & Rubenstein, 1981).…”
Section: Opening the Process Of Innovationmentioning
confidence: 99%